Manajemen Kelas Unggulan dalam Membentuk Karakter Siswa di Madrasah - Muhammad Haidar Baihaqqi; Supriyanto (Economic Reviews Journal, 2025)
The role of education is not only focused on academics, but through education it can also contribute to the formation of students' character. In the world of education, especially in the madrasa environment, it is very important to instill character education in responding to social and moral challenges. The role of madrasas in education has a crucial role, especially in the formation of religious character possessed by students and can integrate several religious values ​​into learning activities. The purpose of this writing is to provide analytical results related to superior class management in forming student character in madrasas. The research method used in this writing adopts a qualitative research method. The findings of the study are that superior class management in forming student character in madrasas can pay attention to several aspects in its application, including teacher exemplary behavior, individual and differentiation approaches, student involvement, and positive discipline. Furthermore, in supporting the formation of student character through the application of superior class management strategies, several things can be considered, including periodic character evaluations, educational rewards and punishments, Islamic character habits, and the application of active learning methods.